Estimation of urinary aldosterone using thin-layer chromatography and fluorimetry. Issue 12 (December 1993) - Mattingly, D; Martin, H; Tyler, C M
Abstract : AIMS--To develop a fluorimetric method for the estimation of urinary aldosterone; to establish a normal range in 24 hour and overnight urine samples; and to investigate the use of overnight urines for detecting hyperaldosteronism. METHODS--Essential steps include hydrolysis of the 18 conjugate to release aldosterone and its oxidation with Benedict's solution, followed by thin-layer chromatography on silica gel and development of fluorescence on the plate with sulphuric acid. RESULTS--There was a linear correlation between the amount of aldosterone and the area under the peak on the chromatogram. The mean intra-assay and interassay coefficients of variation were 4.4% and 6.8%, respectively. The mean aldosterone excretion in 67 adults was 15.7 (SD 8.1) nmol/24 hours. The mean overnight excretion in 65 adults was 2.6 (1.4) nmol/8 hours. The method detected raised concentrations in patients with primary and secondary aldosteronism. CONCLUSIONS--This technique provides an accurate means of assaying urinary aldosterone. Overnight estimations seem to be as effective as 24 hour assays for identifying patients with hyperaldosteronism.